Pregnancy switches adrenergic signal transduction in rat and human uterine myocytes as probed by BK(Ca) channel activity - Zhou, Xiao-Bo (Blackwell Science Inc, 2000)
1. We used large conductance Ca(2+)-activated K(+) (BK(Ca)) channel activity as a probe to characterize the inhibitory/stimulatory G protein (G(i)/G(s)) signalling pathways in intact cells from pregnant (PM) and non-pregnant (NPM) myometrium. 2. Isoprenaline (10 μM) enhanced the outward current (I(out)) in PM cells and inhibited I(out) in NPM cells. Additional application of the α(2)-adrenoceptor (α(2)-AR) agonist clonidine (10 μM) further enhanced the isoprenaline-modulated I(out) in PM cells but partially antagonized I(out) in NPM cells. Clonidine alone did not affect I(out). The specific cAMP kinase (PKA) inhibitor H-89 (1 μM) abolished the effects of isoprenaline and clonidine. The specific BK(Ca) channel blocker iberiotoxin (0·1 μM) inhibited I(out) by ≈80 %; the residual current was insensitive to isoprenaline. 3. Inhibition of G(i) activity by either pertussis toxin or the GTPase activating protein RGS16 abolished inhibitory as well as stimulatory effects of clonidine on I(out). 4. Transducin-α, a scavenger of G(i) βγ dimers, converted the stimulatory action of clonidine on I(out) into an inhibitory effect. Free transducin-βγ enhanced both the stimulatory and the inhibitory effects of isoprenaline on I(out). 5. The results demonstrate that BK(Ca) channel activity is a sensitive probe to follow adenylyl cyclase–cAMP–PKA signalling in myometrial smooth muscle cells. Both G(i)α-mediated inhibition and G(i)βγ-mediated stimulation can occur in the same cell, irrespective of pregnancy. It is speculated that the coupling between α(2)-AR and G(i) proteins is more efficient during pregnancy and that G(i)βγ at high levels simply override the inhibitory action of G(i) α.